Resonance of the '4.2ka event' and terminations of global civilizations during the Holocene, in the palaeoclimate records around PT Tso Lake, Eastern Himalaya - Mehrotra, Nivedita; Shah, Santosh K.; Basavaiah, Nathani; Laskar, Amzad H.; Yadava, Madhusudan G. (My University, 2018)
Climate driven changes have impacted various civilizations and have major influence on human population globally. Remote regions such as the Himalaya also archived these climatic events in various proxies. The Eastern Himalaya region has recorded the Holocene climate change events in numerous proxy records. A multi–proxy record of the early to late mid Holocene climate change from the catchment of PankangTeng Tso (PT Tso) Lake at an altitude of 3935 m asl in the Tawang district of Arunachal Pradesh was studied. A 90 cm sediment profile showed a synchronous pattern of Holocene climate changes in the palynological, environmental magnetic and carbon isotope data recorded. Dominant cold-humid conditions at 4625 cal yr BP followed by a cold-dry period was documented in the proxy data. The vegetation vis-a-vis climate varied throughout the Holocene and cold–dry conditions along with sub-alpine vegetation prevailed in the region around the '4.2ka event'. Human activities and environmental changes in the Tawang district during the Holocene probably impacted the vegetation during this significant period of the development and demise of major global civilizations.
Keywords: 4.2ka event; Bronze age civilizations; Multi–proxy data; Temperature reconstruction; PT Tso lake; Eastern Himalaya